Huaier Effects on Prevention and Inhibition of Spontaneous SARS-CoV-2 Virion Production by Repeated Pfizer-BioNTech mRNA Vaccination - Tanaka, Manami; Tanaka, Tomoo; Teng, Fei; Zhu, Xiaolong; Lin, Hong; Luo, Zhu; Sadahiro, Sotaro; Suzuki, Toshiyuki; Maeda, Yuji; Wei, Ding; et al. (Archives of Clinical and Medical Case Reports, 2023)
Background: Although striking effects of vaccination strategy against pandemic COVID-19, a long-term influence by repeated partial virus mRNA injections are unknown. In addition, the molecular mechanism in accelerated ageing process still remains unclear. Through our clinical research, we observe and reported spontaneous SARS-CoV-2 virion and virion part production after Pfizer-BioNTech mRNA vaccination, observed from 3 weeks after the first injection. A significant destruction in ribosomal RNA structures, enhanced by repeated vaccinations, were also identified. The present study is aimed to define molecular mechanisms for SARSCoV- 2 virion production after injection of mRNA vaccination with a comparison to virion proliferation in non-vaccinated patient with severe COVID-19 pneumonia and fibrosis. Methods: We direct clinical research to define molecular basis for significant anti-cancer efficacy of Huaier (Trametes robiniophila murr). In the present study, we used peripheral blood samples from the volunteer patient, suspected lung cancer by CT image analysis with age-matched normal controls with or without Huaier administration. Molecular characterization was performed analyzed by total RNA and non-coding small RNA sequencing on BGISEQ-500 Platform (about 7.0 GB analysis per sample). Thorough genetic events, Gene Ontology analysis, and functional target gene analysis were performed by using KEGGref) pathway classification (https://www.genome.jp/kegg/). Results: Spontaneous SARS-CoV-2 virion production was identified after Pfizer-BioNTech mRNA vaccination until even 5 months after the 3rd vaccination. We compared this virion production in vivo with infected virus proliferation from severe COVID-19 pneumonia case without any vaccination by total RNA sequencing. No virion and virion particle were detected in normal c